I am attempting to prove that if $a_n$ is a bounded sequence of real numbers then


My approach is to first make some algebraic manipulations, namely we see that

\begin{align*} 1&=\lim_{x\to1^-}\frac{(1-x)\sum_{n=1}^{\infty}a_nx^n}{(1-x)\sum_{n=1}^{\infty}a_nx^n}\\ &=\lim_{x\to1^-}\frac{1}{(1-x)\sum_{n=1}^{\infty}a_nx^n}\left(\frac{1-x}{\frac{1}{\sum_{n=1}^{\infty}a_nx^n}}\right)\\ \end{align*}

The reason I want to do this is that if I were able to apply L'Hopital's rule to


then I would get that

\begin{align*} 1&=\lim_{x\to1^-}\frac{1}{(1-x)\sum_{n=1}^{\infty}a_nx^n}\left(\frac{-1}{-\frac{\sum_{n=1}^{\infty}na_nx^{n-1}}{\left(\sum_{n=1}^{\infty}a_nx^n\right)^2}}\right)\\ &=\lim_{x\to1^-}\frac{\sum_{n=1}^{\infty}a_nx^n}{(1-x)\sum_{n=1}^{\infty}na_nx^{n-1}}\\ \end{align*}

From there we can subtract $1$ from both sides and multiply top and bottom by $(1-x)$ to get that




is bounded, the only way for this quantity to go to zero would be for


to go to $0$, thus yielding what we want.

I am not sure if this use of L'Hopitals is (or can be) justified, since the limit of $$\frac{-1}{-\frac{\sum_{n=1}^{\infty}na_nx^{n-1}}{\left(\sum_{n=1}^{\infty}a_nx^n\right)^2}}$$ as $x\to1^-$ is not required to exist. Is there any way I can make this argument rigorous?

EDIT: If I had the pair of inequalities

$$\limsup_{x\to 1^-}k(x)\frac{f(x)}{g(x)}\leq \limsup_{x\to 1^-}k(x)\frac{f'(x)}{g'(x)}$$

$$\liminf_{x\to 1^-}k(x)\frac{f'(x)}{g'(x)} \leq \liminf_{x\to 1^-}k(x)\frac{f(x)}{g(x)}$$

for differentiable functions $f$, $g$ and $k$ on $[0,1)$ then I could resolve my issue. On wikipedia it states that

$$\liminf_{x\to1^-}\frac{f'(x)}{g'(x)}\leq \liminf_{x\to1^-}\frac{f(x)}{g(x)} \leq \limsup_{x\to1^-}\frac{f(x)}{g(x)}\leq \limsup_{x\to1^-}\frac{f'(x)}{g'(x)}$$

but I can't complete the argument for when the factor of $k(x)$ is added.

  • $\begingroup$ Without L'Hospital rules it clearly go to zero, do you really required l'Hospital rules ? $\endgroup$ – EDX Aug 1 '20 at 18:04
  • $\begingroup$ @EDX Why does it clearly go to $0$? $\endgroup$ – Milo Moses Aug 1 '20 at 18:05
  • $\begingroup$ How could you use L'hospital rule,,,is it in $\frac{0}{0} $ form or $\frac{\infty}{\infty} $ form,. You should know that whether $\sum a_n x^n $ converge or diverge, as $x \to 1- $ $\endgroup$ – A learner Aug 1 '20 at 18:22
  • 1
    $\begingroup$ Where, you first use L'hospital rule in your approach, it can be made totally wrong, by taking $a_n=\frac{1}{n^2} $ $\endgroup$ – A learner Aug 1 '20 at 18:26
  • 1
    $\begingroup$ It is very unclear about what the condition on $a_n$ because being bounded is not sufficient $a_n=1$ is a good example. Uniformarly convergent of $na_n$ (the derivated serie) on $[\epsilon,1]$ with $\epsilon>0$ is clearly sufficient. The interest in your exercise is to set a condition for $a_n$ such the result you want to show can be true without being too obvious (as uniform convergence) $\endgroup$ – EDX Aug 2 '20 at 12:49

My "favourite" counterexample works again. Consider $a_n=(-1)^k$ for $2^k\leqslant n<2^{k+1}$, $k\geqslant 0$.

Then, for $f(x):=\sum_{n=1}^\infty a_n x^n$, we get $g(x):=(1-x)f(x)=x+2\sum_{k=1}^\infty(-1)^k x^{2^k}$. Now let $$h(x)=g(x)+G(\log x),\qquad G(t)=\sum_{n=1}^\infty\frac{2^n-1}{2^n+1}\frac{t^n}{n!}.$$ Then it is easy to check that $h(x)=-h(x^2)$. That is, the function $H(t)=h(e^{-2^{-t}})$ (defined for all real values of $t$) is periodic: $H(t)=H(t+2)$. It is nonconstant, and in fact the linked answer shows that $$H(t)=\frac{2}{\log 2}\sum_{n\in\mathbb{Z}}\Gamma\left(\frac{2n+1}{\log 2}i\pi\right)e^{(2n+1)i\pi t}.$$

Gathering it all, we get $(1-x)f(x)=H\big(-\log_2(-\log x)\big)-G(\log x)$ and $$(1-x)\frac{d}{dx}\big((1-x)f(x)\big)=-\frac{1-x}{x\log x\log 2}H'\big(-\log_2(-\log x)\big)-\frac{1-x}{x}G'(\log x).$$ At $x\to1^-$, the second term vanishes, but the first one oscillates, since $\frac{1-x}{\log x}$ tends to $-1[{}\neq 0]$.

  • $\begingroup$ Just a question what happens as the coefficients are in a decreasing order or an increasing order ? $\endgroup$ – Erik Satie Aug 3 '20 at 8:33
  • $\begingroup$ @user698573: You mean, $a_n$ is increasing (say) and bounded? Then the claim holds (let $a_0=0$): $$(1-x)\big((1-x)f(x)\big)'=(1-x)\sum_{n=1}^\infty n(a_n-a_{n-1})x^{n-1}\underset{x\to 1^-}{\longrightarrow}0$$ by Abel's theorem, since $n(a_n-a_{n-1})\to 0$ as $n\to\infty$ because $\sum_n(a_n-a_{n-1})$ converges. $\endgroup$ – metamorphy Aug 3 '20 at 9:11
  • $\begingroup$ Thanks to confirm my intuition !I was not aware about the Abel's theorem. (+1) $\endgroup$ – Erik Satie Aug 3 '20 at 9:53
  • $\begingroup$ Instead of $k\mapsto 2^k$, one could take a faster-growing sequence, say $k\mapsto 2^{2^k}$. This would make $g(x)$ oscillate between $−1$ and $1$ very steeply. Looks like the stuff under the limit can be made unbounded at any desired rate. $\endgroup$ – metamorphy Aug 3 '20 at 11:32
  • $\begingroup$ How do you know that $H(-\log_2(-\log(x)))$ oscillates as $x$ tends to $1$? $\endgroup$ – Milo Moses Aug 3 '20 at 15:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.